Field Decomposition of Oil Palm Frond and its Effect on Soil Physical Properties - Aman, Mohd Ali (1997)
The growth of agro-based industry in recent years has created a strong competition against the traditional use of oil palm fronds purely to mulch frond avenues in oil palm plantations. Meanwhile, increased mechanization continues to cause soil compaction in harvesting paths which act as sub-agricultural roads . Approximately, 50% of an oil palm area is made up of harvesting paths, thus the resulting soil compaction could have a serious impact on palm growth and yield in the long term. Therefore, the objective of this research was to study the decomposition of oil palm fronds placed on the harvesting path and its effect on soil physical properties. Harvesting paths at Universiti Putra Malaysia oil. palm plantation was mulched with oil palm fronds at four different rates of biomass, Fl (9.2 kg plot-1), F2 (18. 4 kg plot-1), F3 (27. 6 kg plot-1) and F4 (36.8 kg plot-1) representing respectively 25%, 50%, 75% and 100% of the total frond harvested in a year. Unmulched plots were used as control. There were 3 replicates in each treatment and the plots were arranged in randomized complete block design (RCBD). Each plot measures 5.5 m wide and 7.0 m long. The rate of decomposition was determined by destructive tissue sampling of the standing biomass at 0, 3, 6 and 9 months after mulching. At the same time the changes in physical properties within the 0-15 cm soil depth were also monitored. The soil properties analysed were soil organic matter, aggregate stability, bulk density, penetration resistance, available water holding capacity, soil infiltrability and saturated hydraulic conductivity. After nine months of observation, it was found that treatment F1 produced the highest percent of oil palm frond decomposed (73%) while the highest rate of decomposition (8.4 kg month-1) produced by treatment F4. The percent of oil palm frond decomposed increased with time whereas the rate of decomposition decreased. As a result of decomposition, the organic matter of the 0-15 cm soil depth increased by 0.32%, 0.38%, 0.39%, and 0.83% for treatments F1, F2 , F3 and F4 respectively. There was no increase in organic matter for the unmulched plot.